Distribution of BCR::ABL1 Transcript Types and Response to Therapy in Pediatric Patients with Chronic Myeloid Leukemia - Seiser, Esra; Behrens, Yvonne L.; Lukat, Sabine; Sembill, Stephanie; Karow, Axel; Suttorp, Meinolf; Metzler, Markus; Krumbholz, Manuela (Journal of Molecular Diagnostics, 2025)
Achieving a stable deep molecular response with the option to discontinue tyrosine kinase inhibitor treatment is the new therapeutic goal for patients with chronic myeloid leukemia (CML). Several studies have shown that individuals expressing the BCR::ABL1 e14a2 transcript achieve a major molecular response more rapidly than those with the e13a2 transcript. However, technical issues may have confounded these observations, and data for pediatric patients are limited. This study analyzed the distribution of BCR::ABL1 transcript types and their association with baseline hematologic parameters and tyrosine kinase inhibitor treatment response in 102 pediatric patients with CML. Subgroups were compared on the basis of results from routine multiplex PCR and droplet digital PCR (ddPCR). The dynamics of the transcript types under therapy were evaluated in detail in patients and a CML cell line co-expressing e13a2 + e14a2. ddPCR has identified significantly more patients co-expressing e13a2 + e14a2 than classified on the basis of routine diagnostics. This has implications for the categorization of individual subgroups. Comparing transcript dynamics in individuals or a cell line expressing both variants simultaneously revealed no differences in treatment response. When analyzing clinical data based on the transcript classification of patients, it is important to use methods that detect both variants with equal sensitivity. In ddPCR, the transcript variants' ratio is accurately shown because there is no competitive template amplification, as seen in multiplex and quantitative real-time PCR.
CRIS-Team Scopus Importer:2025-02-28

Management of children and adolescents with chronic myeloid leukemia in chronic phase: International pediatric chronic myeloid leukemia expert panel recommendations: CHRONIC MYELOGENOUS LEUKEMIA - Millot, Frédéric; Ampatzidou, Mirella; Moulik, Nirmalya Roy; Tewari, Sanjay; Elhaddad, Alaa; Hammad, Mahmoud; Pichler, Herbert; Lion, Thomas; Tragiannidis, Athanasios; Shima, Haruko; An, Wenbin; Yang, Wenyu; et al. (Leukemia, 2025)
The treatment strategy for children and adolescents with chronic myeloid leukemia in the chronic phase (CML-CP) has evolved from allogeneic hematopoietic stem cell transplantation (HSCT) to tyrosine kinase inhibitors (TKIs). With the advent of next-generation TKIs and new targeted therapies in the CML field, an international pediatric CML expert panel provides recommendations based on the medical literature (including previous pediatric guidelines), national standards, and treatment principles used in adults with CML-CP. Recommendations include diagnosis of the disease and details on managing the initial steps of care of children and adolescents with newly diagnosed CML-CP, including complications such as leukostasis. The treatment recommendations are based on the initiation of therapy with a first- or second-generation TKI according to the allocated European Treatment and Outcome Study (EUTOS) long-term survival score risk group of the patient. The subsequent steps are based on the results of recommended monitoring which can justify a switch to another TKI or a drug in development if there is resistance or toxicity. The panel also provides recommendations regarding the discontinuation criteria for TKIs in children and adolescents in sustained deep molecular response. Allogeneic HSCT is not recommended as the first-line of treatment for children with CML-CP but is to be considered in case of progression to the advanced phase or failure of several lines of treatment. The present treatment and management recommendations are intended to provide advice to clinicians in view of optimizing the care and the outcome of children and adolescents with CML-CP.
CRIS-Team Scopus Importer:2025-03-21